Captação e utilização de águas pluviais para fins não-potáveis - Moreira, Arildo (2015)
This academic work addresses the issue of rainwater harvesting for non-drinking or non-potable purposes allowing its use in not so noble occasions and situations such as toilet flushing, garden watering, washing sidewalks, maintenance of ornamental plant nurseries, as well as the use in industrial activities allow this action, considered as an alternative source this process of abstraction is simple and can be used in homes, condominiums, public or private buildings, clubs, tonando is a viable way to get around the problems with shortages, since the reducing the consumption of clean water that is supplied to the population avoiding the waste of water resources of our planet and may help control the surface urban runoff that affects and causes problems in big cities with few areas for infiltration of these precipitation, examples will be presented of how this process is advantageous, the rules for its use and laws or regulations which are designed to encourage the company to adopt this idea.